The Effect of Breastfeeding Technique Education on the Smoothness of Milk Production in Breastfeeding Mothers of Infants 0-6 Months of Age - Refliya Halipah; Novalia Widiya Ningrum; Fadhiyah Noor Anisa; Siti Noor Hasanah (GLOBAL HEALTH SCIENCE GROUP, 2024)
The correct breastfeeding technique is a way of giving breast milk to the baby with the correct attachment and position of the mother and baby. If the breastfeeding technique is wrong, it can cause nipple blisters, poor milk production and pain that arises when the mother stops breastfeeding with less care. The wrong breastfeeding technique is also one of the factors that cause the milk to come out to be not optimal, thus affecting milk production, causing the baby to not want to suckle. At Puskesmas Sungai Tabuk 2, the exclusive breastfeeding coverage in 2019 was 71.20%, an increase in 2020 to 81.8%, and in 2021 it decreased to 49.6%, one of the causes was due to a lack of knowledge about breastfeeding techniques.Objective: To determine the effect of breastfeeding technique education on the smooth production of breast milk in breastfeeding mothers of infants aged 0-6 months in the Sungai Tabuk 2 Puskesmas working area. Methods: Analytical observational research using case control design with total sampling technique as many as 30 people. The research instrument used leaflets and breast milk fluency questionnaires. The questionnaire has undergone validity testing and obtained a value of reasonable (>0.361) and reliable (0.79). Results: Statistical tests using the chi square test obtained a p value of 0.044 (<0.05) which means that there is an effect on the provision of breastfeeding technique education on the smooth production of breast milk in breastfeeding mothers of infants aged 0-6 months in the working area of Puskesmas Sungai Tabuk 2 Conclusion: The importance of education about breastfeeding techniques from health workers that can be done in posyandu or health services to increase knowledge and understanding of pregnant and lactating women.